Evaluation of quality of life and reasons for self discharge in trauma patient at h.u.s.m. - Kareem, B.A; Isa, Abd. Rahman (1999)
In hospital Universiti Sains Malaysia, self-discharged cases in orthopaedic trauma is high, estimated at 13% of all self discharged cases. Between 1989 to 1991, 75 patients with close and compound fractures, who had made up their mind for self discharge were randomly selected and were interviewed with a questionnaire to identify the factors that influence the patients decision for self-discharge. More than six months later, they were contacted by mail to return to the hospital for reexamination, evaluation of their quality of life, and re-counsel for compliance. Twenty-three patients responded. All of them were males and 78.3% sustained injuries in traffic accident.Fracture of femur accountedd for 56.5% with a majority (95.7%) had close fractures. The line of treatment proposed were conservative for eight and surgical for 15 patients.Reasons cited for self-discharge were many but a majority believed that tradiotional (Bomohs') treatment was superior in healing rate. The quality of life evaluation was compromised by shortening of limb disability, nagging pain, reduction or loss of earning in all of them. Four patient recommended for corrective surgery but only one accepted with good functional outcomes.